SIRT2 knockdown increases basal autophagy and prevents postslippage death by abnormally prolonging the mitotic arrest that is induced by microtubule inhibitors. (30th April 2014) - Inoue, Toshiaki; Nakayama, Yuji; Li, Yanze; Matsumori, Haruka; Takahashi, Haruka; Kojima, Hirotada; Wanibuchi, Hideki; Katoh, Motonobu; Oshimura, Mitsuo
<x xml:space="preserve">Abstract</x> Mitotic catastrophe, a form of cell death that occurs during mitosis and after mitotic slippage to a tetraploid state, plays important roles in the efficacy of cancer cell killing by microtubule inhibitors (MTIs). Prolonged mitotic arrest by the spindle assembly checkpoint is a well‐known requirement for mitotic catastrophe, and thus for conferring sensitivity to MTIs. We previously reported that turning off spindle assembly checkpoint activation after a defined period of time is another requirement for efficient postslippage death from a tetraploid state, and we identified SIRT2, a member of the sirtuin protein family, as a regulator of this process. Here, we investigated whether SIRT2 regulates basal autophagy and whether, in that case, autophagy regulation by SIRT2 is required for postslippage death, by analogy with previous insights into SIRT1 functions in autophagy. We show, by combined knockdown of autophagy genes and SIRT2, that SIRT2 serves this function at least partially by suppressing basal autophagy levels. Notably, increased autophagy induced by rapamycin and mild starvation caused mitotic arrest for an abnormally long period of time in the presence of MTIs, and this was followed by delayed postslippage death, which was also observed in cells with SIRT2 knockdown. These results underscore a causal association among increased autophagy levels, mitotic arrest for an abnormally long period of time after exposure to MTIs, and resistance to MTIs. Although autophagy acts as a tumor suppressor mechanism, this study highlights its negative aspects, as increased autophagy may cause mitotic catastrophe malfunction. Thus, SIRT2 offers a novel target for tumor therapy.